Interdependência e integração entre marketing e operações na operação de serviços - D’Avila, Lívia Castro (Universidade do Vale do Rio dos Sinos, 2013)
Marketing and operations integration is an important research topic that has gained attention the field of Administration since the 1970s, especially because the two functions are directly responsible for creating or adding value to what is delivered. The issue is clear in practice and identified as a topic of discussion by theory. Service characteristics that are different from goods, such as intangibility, inseparability and customer participation at runtime increase the complexity and the need for better interface between the marketing and operations functions. A functional perspective of marketing and operations functions was taken, instead of a departmental division of the two areas. This dissertation seeks to contribute on the identification of the interdependence between marketing and operations functions, and investigate the relationship between greater integration and operational performance of the service. To develop the proposal the study first identified interdependence, integration and performance constructs. A survey was conducted in educational services context and focus on two services conducted by a university: Vestibular and Matrícula. 51 respondents, representing the networks of actors involved in conducting marketing activities and operations in the implementation of the analyzed processes, participated on a survey. Data were analyzed based on the use of Social Network Analysis that allowed centrality of the network evaluation, confirming the existence of interdependence on the implementation of the processes. It also allows the evaluation the network integration and the analysis of the intensity of the relationships between actors to perform the tasks. Based on the results, trust on the information, understanding on the other’s activity and are important factors in improving integration. So that, besides the limitations of this study, there is an interdependence between functions, however, greater integration between functions is not responsible for better performance. So it cannot be said that increasing integration impacts on better performance, but it can be seen that better integration generates better performance.
Keywords: Marketing; Operações; Integração; Serviços; Interdependência; Análise de redes sociais; Desempenho; Operation; Integration; Services; Interdependence; Social network analysis; Performace; ACCNPQ::Ciências Sociais Aplicadas::Administração